2012
DOI: 10.1038/bcj.2012.37
|View full text |Cite
|
Sign up to set email alerts
|

The t(4;14) translocation and FGFR3 overexpression in multiple myeloma: prognostic implications and current clinical strategies

Abstract: Multiple myeloma (MM) is a heterogeneous plasma cell disorder characterized by genetic abnormalities, including chromosomal translocations, deletions, duplications and genetic mutations. Translocations involving the immunoglobulin heavy chain region at chromosome 14q32 are observed in approximately 40% of patients with MM. Translocation of oncogenes into this region may lead to their increased expression, contributing to disease initiation, disease progression and therapeutic resistance. The t(4;14) translocat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
90
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(92 citation statements)
references
References 70 publications
(150 reference statements)
1
90
1
Order By: Relevance
“…This mutation leads to the formation of an aberrant intermolecular cysteine bridge that results in ligand-independent constitutive dimerization and activation of the receptor [49]. FGFR3 mutations have also been identified in many other cancer types, including cervical cancers [50], multiple myeloma (MM) [51,52], prostate cancers [53], spermatocytic seminomas [54] and oral squamous carcinomas [55]. Other mutations located in the TK domain can change the FGFR conformation, leading to a constitutive ligand-independent receptor activation, as observed for FGFR4 in the childhood rhabdomyosarcoma [56].…”
Section: Chemotherapeuticsmentioning
confidence: 99%
“…This mutation leads to the formation of an aberrant intermolecular cysteine bridge that results in ligand-independent constitutive dimerization and activation of the receptor [49]. FGFR3 mutations have also been identified in many other cancer types, including cervical cancers [50], multiple myeloma (MM) [51,52], prostate cancers [53], spermatocytic seminomas [54] and oral squamous carcinomas [55]. Other mutations located in the TK domain can change the FGFR conformation, leading to a constitutive ligand-independent receptor activation, as observed for FGFR4 in the childhood rhabdomyosarcoma [56].…”
Section: Chemotherapeuticsmentioning
confidence: 99%
“…Translocation events implicating the FGFR1 gene and various fusions of FGFR1 are found in myeloproliferative syndromes (12); chromosomal translocations of FGFR1 or FGFR3 and the transforming acidic coiled-coil genes (TACC1 or TACC3) are oncogenic in glioblastoma multiforme, bladder cancer, head and neck cancer, and lung cancer (13)(14)(15)(16); oncogenic mutations of FGFR2 and FGFR3 are observed in lung squamous cell carcinoma; FGFR2 N549K is observed in 25% of endometrial cancers; FGFR3 t(4;14) alterations are reported in 15-20% of multiple myeloma (17)(18)(19); FGFR4 Y367C mutation in the transmembrane domain drives constitutive activation and enhanced tumorigenic phenotypes in a breast carcinoma cell line (20)(21)(22); and K535 and E550 mutants are reported to activate FGFR4 in rhabdomyosarcoma (23). FGFR amplification is reported in various cancers (24,25): FGFR1 is amplified in colorectal, lung, and renal cell cancers (26,27); FGFR2 is amplified in gastric cancer and colorectal cancer (28,29); FGFR3 is commonly amplified in bladder cancer and also is reported for cervical, oral, and hematological cancers (30)(31)(32); and FGFR4 is amplified in hepatocellular carcinoma, gastric cancer, pancreatic cancer, and ovarian cancer (33)(34)(35)(36)(37). FGFR also is involved in autocrine activation of STAT3 as a positive feedback in many drug-treated cancer cells which are driven by diverse oncogenes such as EGFR, ALK, MET, and KRAS (38).…”
Section: Significancementioning
confidence: 99%
“…Indeed, MMSET domain (also referred to as Wolf-Hirschhorn syndrome candidate 1) and FGFR3 reside on either side of the 4p16 breakpoint. After the translocation, MMSET remains on the derivative chromosome 4, while FGFR3 moves to the derivative chromosome 14 (93)(94)(95). The MMSET protein has histone methyltransferase activity and may act as a transcriptional regulator controlling cell cycle and apoptosis (96,97).…”
Section: T(10;14)(p12;q32) T(10;22)(p12;q11) [Igh/bmi1 Proto-oncogenementioning
confidence: 99%